Enhancing Students’ Learning Outcomes in Fundamental Social Studies Concepts through Virtual Learning on Historical Content - Ahmad, Andy; Syaikhu, Ahmad; Utomo, Fajar Wahyudi (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2025)
The development of information and communication technology (ICT) has transformed education through the implementation of online learning, particularly with Virtual Classrooms. This study aims to evaluate the effectiveness of Virtual Classroom use in the Basic Concepts of Social Studies course for students of STKIP Kusumanegara. The research involved 30 students who participated in online lectures via a digital platform equipped with features such as learning materials, discussion forums, quizzes, and online assignments. A descriptive qualitative approach was employed to analyze students’ conceptual understanding, engagement, and competence achievement. The findings reveal that Virtual Classrooms provide learning flexibility, broaden access to resources, and foster student independence. However, several challenges were identified, including limited internet access, inadequate devices, and low participation in online discussions. These constraints influenced conceptual comprehension and lecturer–student interaction. Despite these obstacles, the use of Virtual Classrooms remains effective as an alternative as well as a complementary medium to face-to-face learning, especially when supported by active and collaborative learning strategies. The study concludes that Virtual Classrooms hold significant potential for improving the quality of teaching the Basic Concepts of Social Studies, though further development of innovative methods and approaches is necessary. These findings are expected to serve as a foundation for enhancing technology-based learning in higher education, particularly in teacher education programs.